Patient reported health status and cardiovascular risk factors in a remote area of South America: a cross-sectional study. (14th October 2021) - Holm, A E; Gomes, L; Lima, K O; Matos, L O; Wegener, A; Vieira, I V M; Souza, R M; Marinho, C R F; Biering-Soerensen, T; Silvestre, O M; Brainin, P
Abstract: Background: Several studies have indicated that self-perception of health is related to cardiovascular disease. Despite cardiovascular disease is the leading cause of mortality in South America, the relationship between patient reported health and cardiovascular risk is sparsely explored, specifically in indigenous areas. Purpose: We assessed if self-rated health is associated with cardiovascular risk factors in a remote area in South America. Methods: We included participants by cluster-randomization of community health care clinics from June to December 2020. Sociodemographic variables and information on cardiovascular risk factors were collected by questionnaires and physical examination. All participants rated their present health status according to the validated EQ5D-VAS instrument, ranging from 0 (worst) to 100 (best). Results: A total of 492 participants (mean age 41±15 years; 38% men) were included. The mean value of self-rated health was 80 (range 0 to 100) and the prevalence of cardiovascular risk factors were: Hypertension (19%), hypercholesterolemia (15%), smoking (37%), low intake of vegetables (defined as <3 times per week; 54%), no sport activity (62%), diabetes (6%) and obesity (24%). In logistic regression models adjusted for sex, age and socioeconomic status, higher self-rated health was significantly associated with lower risk of hypertension, hypercholesterolemia, smoking, obesity and greater vegetable intake (P<0.05; Figure 1). No association was found with sport activity or diabetes. The total number of cardiovascular risk factors increased with lower self-rated health (beta = 0.100 [0.04 to 0.15], P<0.001 per 10 decrease in self-reported health). Conclusion: Self-rated health was significantly associated with a greater burden of cardiovascular risk factors and may influence ideal cardiovascular health. Future studies should assess if patient reported health status constitutes an independent risk factor for heart disease in this specific population, and studies elucidating gaps on self-perception of cardiovascular health are encouraged. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Independent Research Fund Denmark